STRATEGI PENGOPTIMALAN BANK SAMPAH MITRA HARIWANG DI DESA PASIR LAWANG KECAMATAN PURWADADI KABUPATEN CIAMIS - Ujang Irman Saputra (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Waste banks are one of the innovative solutions in community-based waste management that can provide economic value while reducing environmental problems. This study aims to analyze optimization strategies for Mitra Hariwang Waste Bank in Pasir Lawang Village, Purwadadi District, Ciamis Regency. The research method used is qualitative method with descriptive analytical approach through field observation, in-depth interviews with waste bank managers and customers, and documentation studies. The results showed that Mitra Hariwang Waste Bank has great potential but still faces obstacles in terms of operational management, community participation, and marketing of recycled products. The recommended optimization strategies include: (1) improving the capacity of management human resources, (2) diversifying the types of waste received, (3) developing management information systems, (4) strengthening marketing networks, and (5) intensifying community education programs. The implementation of this strategy is expected to increase the effectiveness and sustainability of Mitra Hariwang Waste Bank as a community-based waste management model.